Early results on the effectiveness of fiberglass nest boxes for barn owl establishment at FPSB estates - Eow , W . S . (2013)
Following favourable results obtained from a one year monitoring of fibreglass nest boxes' acceptance by barn owls in FPSB Lepar Utara 11, two other FPSB estates, namely Bera Selatan 6 and Maokil 6, followed suit. This paper reports the results from the first quarterly census of barn owl population and rat damage levels carried out by FASSB in the three projects.